Examining the Relationship Between Science Literacy, Science Process Skills, and Higher-Order Thinking Skills in Elementary Teacher Education Students - Idam Ragil Widianto Atmojo; Roy Ardiansyah; Hanifaw Rahma Setyaningrum; Dwi Yuniasih Saputri (AL-ISHLAH: Jurnal Pendidikan, 2024)
Science literacy is crucial for prospective elementary school teachers to enhance their higher-order thinking skills. Science education that emphasizes the development of higher-order thinking skills is based on science process skills. This research aims to determine the relationship between science literacy and science process skills on HOTS (Higher Order Thinking Skills) cognitive learning outcomes. The study employs a quantitative approach with a correlational method. Data collection for the variables of science literacy and HOTS cognitive learning outcomes was conducted through written tests, while data collection for the science process skills variable was carried out through performance tests developed by the researcher. The population consists of all 2022 Elementary School Teacher Education Study Program or PGSD students in Sebelas Maret University, with random cluster sampling. Data analysis employs multiple correlation analysis. The results indicate a positive and significant relationship between science literacy and science process skills on HOTS cognitive learning outcomes, with a significance value of 0.000 0.05 and a Pearson correlation value of 0.495. There is a positive and significant combined relationship between science literacy and science process skills on HOTS (Higher Order Thinking Skills) cognitive learning outcomes, with a moderate level of correlation. The findings of this study have important implications for students' enhancement of their science process skills, science literacy, and HOTS cognitive learning outcomes. This research positively impacts academic programs by encouraging students and implementing relevant teaching strategies and methods, thereby improving science literacy, science process skills, and HOTS cognitive learning outcomes.